Myocarditis after triple immunisation. Issue 4 (April 1986) - Amsel, S G; Hanukoglu, A; Fried, D; Wolyvovics, M
Abstract : We describe a 3 month old infant who developed myocarditis several hours after diphtheria, tetanus, and pertussis vaccination. The time of occurrence of symptoms, the clinical course, and the negative virological studies suggest a possible cardiogenic adverse reaction to the vaccine.